A CROSS-SECTIONAL STUDY: KNOWLEDGE AND ATTITUDE TOWARD PARTICIPATION IN THE COVID-19 VACCINATION PROGRAM AMONG MEDICAL STUDENTS - Fatimah, Husnul; Diauddin; Jayadi, Yusef Dwi; Aflanie, Iwan; Bakhriansyah, Mohammad; Istiana; Rahman, Fauzie; Anhar, Vina Yulia (Journal of Public Health Research and Community Health Development, 2023)
Background: COVID-19 pandemic in Indonesia has increased. Therefore, some efforts are needed including the COVID-19 Vaccination Program to overcome this issue. Until June 29th, 2021, 28.304.774 Indonesians have received the first dose of the vaccine, and 13.329.738 for the second dose of vaccine, out of the national target of 181.554.465. It indicates that the coverage is still far from the target. The knowledge and attitude of the individual are one of the key factors for a person to participate in the program. Purpose: To analyze the correlation between the level of knowledge and attitudes toward their participation in the COVID-19 Vaccination Program among medical students. Methods: This is descriptive analytic with cross-sectional approach. The samples were 339 Medical Students Universitas Lambung Mangkurat. Sampling technique was collected using stratified random sampling technique. Data was retrieved online using Google Forms. Data were then analyzed using statistical software the IBM SPSS version 23. The fisher exact test was used to test the significance of the relationship. Results: We included 339 medical students, in which 264 students (77.9%) participated in the vaccination program but 75 students (22.1%) didn't. The statistical test showed that p-value of the relationship between knowledge and attitudes with participation of medical student in the COVID-19 vaccination program with p-value= 0.055 and p-value= 0.025. Conclusion: There is no correlation between knowledge and participation of medical students in the COVID-19 Vaccination Program, but there is a correlation between attitudes toward the participation of medical students in the COVID-19 Vaccination Program.